Primerjava gledaliških sistemov - Maanen, Hans van (Amfiteater (Ljubljana), 2015)
This article is meant as a starting point in the process of researching how theatre systems influence the functioning of theatre. The notion "theatre system" is understood as the set of organisational relationships within and between the domains of production, distribution and reception of theatre. Because the hypothesis of the Project on European Theatre Systems (STEP) is that the differences in these organisational patterns at least partly determine the types of theatre offered to city populations and their use of the supply, the present article attempts to make a start with a comparison between the theatre systems in Aarhus (Denmark), Bern (Switzerland), Debrecen (Hungary), Groningen (The Netherlands), Maribor (Slovenia), Tartu (Estonia) and Tyneside (United Kingdom). One of the findings of this comparison is that the structures of financial support for theatre by the various authorities do not differ very strongly among the countries on the European continent. However, the so-called city theatres in Central and Eastern Europe seem to have a more dominant position than in the Western European countries. For smaller, independent theatre organisations this is the other way round. In addition, the position of Bern is remarkable, because of the exceptional number of venues and theatre performances in this city. In Debrecen and Maribor, cultural centres appear to play quite an important role in the theatre life of these cities.
Keywords: gledališče; gledališka prizorišča; gledališki sistemi; international comparative theatre survey; mednarodne primerjave; STEP; subsidisation; subvencioniranje; theater; theatre systems; theatre venues